PARENTHETICALS IN M. A. BULGAKOV’S NOVEL “THE MASTER AND MARGARITA” - Irina Yuryevna Kononova (Galaxy International Interdisciplinary Research Journal, 2024)
This paper describes the formal and functional characteristics of parentheticals in M. A. Bulgakov’s novel “The Master and Margarita” and demonstrates the following functional types of parentheticals in this novel: parenthetical remarks, metalinguistic, metaspeech, metatextual, and communicative parentheticals.